Expression and heterodimer-binding activity of Ku70 and Ku80 in human non-melanoma skin cancer. Issue 11 (23rd February 2006) - Parrella, P; Mazzarelli, P; Signori, E; Perrone, G; Marangi, G F; Rabitti, C; Delfino, M; Prencipe, M; Gallo, A P; Rinaldi, M; Fabbrocini, G; Delfino, S; et al.
Abstract : Background: Experimental data suggest that exposure to ultraviolet radiation may indirectly induce DNA double-strand breaks. Aim: To investigate the contribution of the non-homologous end-joining repair pathway in basal and squamous cell carcinomas. Methods: Levels of Ku70 and Ku80 proteins were determined by immunohistochemical analysis and Ku70–Ku80 heterodimer-binding activity by electrophoretic mobility shift assay. Matched pathological normal margins and skin from healthy people were used as controls. Results: A significant increase in Ku70 and Ku80 protein levels was found for both tumour types as compared with normal skin (p<0.001). Squamous cell carcinoma showed increased immunostaining as compared with basal cell tumours (p<0.02). A direct correlation was found between Ku70 and Ku80 protein levels and expression of the proliferation markers Ki-67/MIB-1 (p<0.02 and p<0.002, respectively) in basal cell carcinoma. DNA binding activity was increased in basal cell carcinoma samples as compared with matched skin histopathologically negative for cancer (p<0.006). In squamous cell carcinomas, however, the difference was significant only with normal skin (p<0.02) and not with matched pathologically normal margins. Conclusions: Overall, an up regulation of the Ku70 and Ku80 protein levels seems to correlate only with tumour proliferation rate. As non-homologous end joining is an error-prone mechanism, its up regulation may ultimately increase genomic instability, contributing to tumour progression.